Antibacterial activities of gold and silver nanoparticles against Escherichia coli and bacillus Calmette-Guérin - Zhou, Yan; Kong, Ying; Kundu, Subrata; Cirillo, Jeffrey D; Liang, Hong (Journal of nanobiotechnology, 2012)
Background Diseases such as tuberculosis (TB) have always had a large impact on human health. Bacillus Calmette-Guérin (BCG) is used as a surrogate for TB during the development of anti-TB drugs. Nanoparticles (NPs) have attracted great interest in drug development. The purpose of this study was to examine the potential of NPs as anti-TB compounds by studying the interacting mechanisms between NPs and bacteria. Results We investigated effects of gold and silver NPs on BCG and Escherichia coli . Experimentally, particle size and shape were characterized using transmission electron microscopy (TEM). Different concentrations of NPs were applied in bacterial culture. The growth of E. coli was monitored through colony forming units (CFU). The mechanism of interaction between NPs and bacteria was analyzed through bacterial thin sections followed by TEM and scanning electron microscopy. Antibacterial effects on BCG were observed by recording fluorescent protein expression levels. Conclusions The results suggest NPs have potential applications as anti-TB compounds. The antibacterial effects and mechanism of action for NPs were dependent upon composition and surface modifications.